The Evolving Complexities of MAID Care in Canada From a Nursing Perspective - Barbara Pesut; Sally Thorne; Kenneth Chambaere; Margaret Hall; Catharine J. Schiller (SAGE Publishing, 2024)
Medical Assistance in Dying (MAID) legislation has evolved rapidly in Canada with significant impacts on nursing practice. The purpose of this paper is to describe evolving complexities in legislative context and practice standards that influence the experiences nurse practitioners and registered nurses have with MAID. Qualitative interviews were conducted with 25 registered nurses and 10 nurse practitioners from diverse contexts across Canada. Participants described their practices and considerations when discussing MAID as part of advance care planning; their use of, and challenges with, waivers of consent; their practice considerations in negotiating the complexities of clients for whom death is not reasonably foreseeable; and their moral wrestling with the inclusion of MAID for persons whose sole underlying medical condition is mental illness. Findings illustrate the moral complexities inherent in the evolving legislation and the importance of robust health and social care systems to the legal and ethical implementation of MAID in Canada.